Engaging clinicians in motivational interviewing: Comparing online with face‐to‐face post‐training consolidation. (14th January 2016) - Clancy, Richard; Taylor, Andrew
Abstract: Motivational interviewing (MI) is an evidence‐based intervention that has been widely recommended in clinical settings where consumer behaviour change is a goal of treatment. Training clinicians in MI, as with other translational endeavours, does not always result in changes to clinical practice. The present study compares two post‐training approaches to consolidate MI skills following a training workshop. We randomly assigned 63 clinicians working in mental health or drug and alcohol services to receive either face‐to‐face group consolidation sessions or to access a series of online consolidation resources. We compared clinician engagement and devised a new instrument to measure clinician outcomes. Participants who completed follow‐up consolidation retained knowledge, attitudes, and practices, regardless of consolidation method. Face‐to‐face consolidation sessions were superior to online materials in engaging participants (mean sessions attended was 2.1 (maximum possible = 3) compared to a mean of 1.38 sessions, respectively ( t (61) = −2.73, P  = 0.008, d = 0.72, 95% confidence interval: 0.19–1.25). Engagement to the completion of consolidation sessions was also influenced by previous training in MI. For every additional hour of previous MI training, there was a 10% increase in the odds that the participant would complete the final consolidation session.